The swing voter's curse revisited: transparency's impact on committee voting - Bandyopadhyay, Siddhartha; Deb, Moumita; Lohse, Johannes; McDonald, Rebecca (AWI discussion paper series, 2024)
Majority voting is considered an efficient information aggregation mechanism in committee decision-making. We examine if this holds in environments where voters first need to acquire information from sources of varied quality and cost. In such environments, efficiency may depend on free-riding incentives and the 'transparency' regime - the knowledge voters have about other voters' acquired information. Intuitively, more transparent regimes should improve efficiency. Our theoretical model instead demonstrates that under some conditions, less transparent regimes can match the rate of efficient information aggregation in more transparent regimes if all members cast a vote based on the information they hold. However, a Pareto inferior swing voter's curse (SVC) equilibrium arises in less transparent regimes if less informed members abstain. We test this proposition in a lab experiment, randomly assigning participants to different transparency regimes. Results in less transparent regimes are consistent with the SVC equilibrium, leading to less favourable outcomes than in more transparent regimes. We thus offer the first experimental evidence on the effects of different transparency regimes on information acquisition, voting, and overall efficiency.
Keywords: Graue Literatur